Effects of Juhongtanke oral solution on alleviating the symptoms of community-acquired pneumonia: A multicenter, prospective, randomized controlled trial - Min Liang; Linhui Hu; Linhui Hu; Ning Luo; Hualiang Lv; Zhihua Chen; Jianping Mo; Meiyan Yang; Ying Lin; Chunbo Chen; Chunbo Chen; Chunbo Chen; et al. (Frontiers Media S.A., 2022)
Introduction: The timely alleviation of symptoms is essential for managing community-acquired pneumonia (CAP). Juhongtanke oral solution is a traditional marketed Chinese patent medicine believed to ease CAP symptoms. The currently available evidence is based on a few retrospective studies of patients with various types of pneumonia, whereas robust randomized controlled trials (RCTs) that support this notion are lacking.Material and methods: In this multi-center, prospective RCT, patients were randomly allocated to receive routine treatment alone or a combination of Juhongtanke oral solution (20 mL q8h) for 5 days and maintained for an additional 3-day safety observation period. The primary outcome was Breathlessness, Cough, and Sputum Scale (BCSS) score evaluated on day 5. Secondary outcomes included the evaluation of cough and dyspnea items in the Visual Analogue Scale (VAS) from days 1-5, remission rate in BCSS and VAS during the treatment course, and the length of hospitalization and in-hospital mortality.Results: Of 272 patients assessed for eligibility, 240 were enrolled in the study (n =120 per group). The mean difference in BCSS evaluated on day 5 was a median 1 point [95%CI (1.00, 2.00)], significantly lower in the treatment group compared with the control group (p < 0.001). Similar results were observed in VAS on day 5, with statistics of a median 2 points [95%CI (1.40, 2.50)] in the cough item and a median 1 point [95%CI (0.50, 2.00)] in the dyspnea item, significantly lower in the treatment group compared with the control group (both p < 0.001). The treatment group had a favorable outcome in BCSS and VAS remission rate assessments compared with the control group, with 99.50% vs. 89.17% in BCSS (p = 0.01), 98.33% vs. 75% in the cough item of VAS (p < 0.001), and 88.33% vs. 62.50% in the dyspnea item of VAS (p < 0.001), respectively. No notable adverse effects were observed during the study. No differences were observed in the length of hospitalization between groups (with a median of 7 days for both groups, p = 0.871).Conclusion: Juhongtanke oral solution may be considered to alleviate the clinical symptoms of CAP.